Spatial summation and spatial discrimination of pain sensation - Defrin, Ruth; Givon, Ronit; Raz, Netta; Urca, Gideon (Pain (Amsterdam), 2006)
The aims of this study were to explore: (a) the interrelation between spatial summation (SS) and spatial discrimination (SD) of pain, (b) whether the two phenomena are subserved by different sensory channels. SS and SD of pain were measured with contact heat stimuli delivered at slow (0.50 °C/s) and fast (40 °C/s) rise times. Pressure nerve block of the radial nerve was employed to assess whether differential activation of C and Aδ fibers is obtained by these different rates of rise. Two discrete stimuli (each 3 × 3 cm) were applied to the forearm with separation distances between them varying from 0 to 30 cm. A single stimulus or two applied simultaneously were employed. For each distance heat-pain threshold (HPT) and suprathreshold pain ratings were obtained and subjects were asked to report the number of pain spots perceived (SD). SS of HPT occurred at separations smaller than 10 cm whereas significant SD occurred only from a separation of 10 cm and up. SS of suprathreshold sensations was completely accounted for by threshold changes. Stimulation rate did not affect SS or SD. Following nerve block, thresholds obtained with the fast rise stimulation increased significantly (HPT rose from 46.2 to 50.5 °C) but those obtained with slow rise stimuli were not affected by the block, indicating that C and Aδ fibers were activated selectively. The results suggest that: (a) SS and SD are mutually exclusive functions of the nociceptive systems, (b) C and Aδ nociceptors are probably similarly involved in these functions.